Analysis of Notary's Responsibility as Land Deed Official for Collateral That Cannot Be Bound by Mortgage Rights (Study of Credit Agreement Number Xx Dated March 27, 2020 Between Mr. M and PT. BANK N Bawan Branch Office, Agam Regency - Fiqri, Rizalul (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2024)
This study discusses the analysis of the responsibility of Notaries/PPAT SH for collateral that cannot be bound by mortgage rights, because the object of the mortgage right after the certificate is issued is designated as a protected forest area. Notaries/PPAT SH have issued a cover note for the collateral and have signed a deed of power of attorney to encumber the mortgage right. The research method used in this thesis is the normative juridical legal research method. This research approach uses a case approach. The types of data used in this study are primary data which include; Civil Code; Banking Law, Notary Law, Mortgage Law and secondary data containing books and other supporting documents. Data collection using interview techniques and document studies or library materials. Qualitative data analysis regarding the responsibility and legal consequences of the Notary's responsibility as PPAT for collateral that cannot be bound by mortgage rights. The results of the study include the cover note issued by the Notary/PPAT SH is not an authentic deed, but only a statement letter. Therefore, the form of responsibility in the form of moral sanctions in the form of the bank's distrust of the notary because the notary cannot complete what is contained in the cover note as expected. If the credit agreement is not fulfilled by Mr. M, then the results of the takeover of collateral or assets owned by Mr. M cannot be auctioned to pay off the debt because the position of PT. Bank N Branch Office of Bawan, Agam Regency is only as a concurrent creditor.